A new species of tafalisca walker, 1869 from the Iguaçu National Park, Brazil (Grylloidea, Eneopteridae, Tafaliscinae) - Dias, Pedro Guilherme B.S.; De Mello, Francisco De Assis G. [UNESP] (Magnolia Press, 2010)
The aim of this work was to describe a new cricket species from the Iguaçu National Park, Southeastern Brazil. We characterize the genitalia and external morphology of Tafalisca paranaensis n. sp. and the genitalia of Tafalisca paulista Rehn, 1918 providing a comparison between these species. Copyright © 2010 Magnolia Press.
Keywords: Atlantic Forest; Cricket; Neotropical; Tafaliscini; Taxonomy